PERBANDINGAN PEMILIHAN UMUM PRESIDEN DI INDONESIA DENGAN KOREA SELATAN - Sultoni Fikri; Idzhati Fitri Nabilah; Ika Sistia Wulan Sari; Tio Fernida Siregar (Universitas Batanghari Jambi, 2022)
The purpose of writing this journal is to find out where the differences and similarities between the presidential election system are in 2 (two) countries, namely Indonesia and South Korea. The focus of the questions in this journal is: how is the general election system implemented in Indonesia and South Korea (which includes explaining the history, system and mechanism of general elections in Indonesia and South Korea as well as, what are the differences in the presidential election system that used by Indonesia and South Korea. The research in this journal uses a normative juridical approach where the reference in writing is the legal basis of 2 (two) countries namely Indonesia and South Korea, in Indonesia the general election system uses the constitutional basis of the Constitution The Republic of Indonesia in 1945, Law Number 42 of 2008 concerning General Elections for President and Vice President, Law Number 7 of 2017 concerning General Elections, while South Korea uses the Constitution of the Republic of Korea [Hangul: Daehanmingug Heonbeob]. So in s conclude that in writing this journal there are similarities and differences in the history, mechanisms, regulations, systems of the general elections of Indonesia and South Korea.